Key Strike Forces and Their Relation to High Level of Musculoskeletal Symptoms - Yafa Levanon; Amit Gefen; Yehuda Lerman; Sigal Portnoy; Navah Z. Ratzon (Elsevier, 2016)
Background: This study aimed to investigate the relation between key strike forces and musculoskeletal symptoms (MSS). Moreover, this study presents a key strike force measurement method to be used in a workplace setting. The correlation between key strike force characteristics and MSS was previously studied, but the measurement methods used either a single-key switch or force platforms applied under the keyboard. Most of the studies were conducted in a laboratory setting. The uniqueness of measurement methods in the current study is their ability to measure forces applied to a specific key in a workplace setting and to provide more information about specific key strike forces during typing. Methods: Twenty-four healthy computer workers were recruited for the study. The demographic questionnaire, and self-reported questionnaires for psychosocial status (General Nordic Questionnaire for Psychological and Social Factors at Work) and for detecting MSS were filled up, which later helped in dividing the participants into two groups (12 participants with pain and 12 without pain). Participants typed a predetermined text that utilized the instrumented keys multiple times. The dynamic forces applied to the keys were recorded and collected, using four thin and flexible force sensors attached to the preselected keys according to their location. Results: The results demonstrated that participants with high levels of MSS, specifically in the back and neck, in the last year exerted significantly higher key strike forces than those with lower levels of symptoms (p<0.005). Conclusion: The key strike force exerted while typing on a keyboard may be a risk factor for MSS, and should therefore be considered in ergonomic evaluations and interventional programs.